A systematic review of the biomechanical research methods used in strongman studies. Issue 1 (2nd January 2020) - Hindle, Benjamin R.; Lorimer, Anna; Winwood, Paul; Keogh, Justin W. L.
ABSTRACT: As the sport of strongman is becoming increasingly popular, and such exercises are being commonly used by strength and conditioning coaches for a wide range of athletic groups, a greater understanding of the biomechanics of strongman exercises is warranted. To improve the quality of research, this systematic review summarised the research methodology used in biomechanical studies of strongman exercises and identified potential improvements to current approaches. A search of 5 databases found 10 articles adherent to the pre-defined inclusion criteria. The studies assessed 8 strongman exercises and included male participants of relatively similar body mass but varying training backgrounds. Due to the complexity of strongman exercises and the challenges in collecting advanced biomechanical data in the field, most studies used simplified measurement/analysis methods (e.g., 2D motion capture). Future strongman biomechanical studies should: assess under/un-researched strongman exercises; include a greater number of experienced and female strongman athletes; utilise more advanced (e.g., 3D motion capture and/or inertial sensor) technology so to provide a broader range and greater quality of data. Such approaches will provide strength and conditioning coaches, strongman coaches and athletes with a greater understanding of strongman exercises, thereby further improving exercise prescription, athlete performance and minimising risk of injury.